2019
DOI: 10.1016/j.msea.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic investigation of damage mechanisms and anisotropic evolution of damage in DP600

Abstract: Weight reduction and fuel consumption play an important role on material selection in automotive industry. In this respect, ferritic-martensitic dual phase steels are gaining popularity thanks to their versatile combination of strength and formability. In this study, we investigate evolution of damage and active damage mechanisms in a commercial DP600 steel. Interrupted tensile tests are conducted in both rolling (RD) and transverse directions (TD). Subsequently, damage mechanisms and void evolution is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…It is concluded in [8] that for the DP800 they studied no definitive failure mechanism could be found meaning all of them were equally possible. Asik [9], who studied damage mechanisms for the specific DP steel that are used in this study, found that all damage mechanisms are equally likely to occur. A general overview of literature on this subject can be found in [10].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…It is concluded in [8] that for the DP800 they studied no definitive failure mechanism could be found meaning all of them were equally possible. Asik [9], who studied damage mechanisms for the specific DP steel that are used in this study, found that all damage mechanisms are equally likely to occur. A general overview of literature on this subject can be found in [10].…”
Section: Introductionmentioning
confidence: 92%
“…The second type was inside the ferrite grains with a martensite neighbor and towards the boundary between ferrite and the neighboring martensite island. The choice of these locations was based on the experimental observations, which show that in DP steels there is more than one active damage mechanism [9,28]. By adding the most common damage mechanisms into the model we aim to clarify and give an explanation on how one of the mechanisms becomes dominant over the others and on the effect of martensite banding on the evolution of these damage mechanisms.…”
Section: Microstructurementioning
confidence: 99%
See 3 more Smart Citations